If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(t + -1) = 6(t + 3) Reorder the terms: 8(-1 + t) = 6(t + 3) (-1 * 8 + t * 8) = 6(t + 3) (-8 + 8t) = 6(t + 3) Reorder the terms: -8 + 8t = 6(3 + t) -8 + 8t = (3 * 6 + t * 6) -8 + 8t = (18 + 6t) Solving -8 + 8t = 18 + 6t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-6t' to each side of the equation. -8 + 8t + -6t = 18 + 6t + -6t Combine like terms: 8t + -6t = 2t -8 + 2t = 18 + 6t + -6t Combine like terms: 6t + -6t = 0 -8 + 2t = 18 + 0 -8 + 2t = 18 Add '8' to each side of the equation. -8 + 8 + 2t = 18 + 8 Combine like terms: -8 + 8 = 0 0 + 2t = 18 + 8 2t = 18 + 8 Combine like terms: 18 + 8 = 26 2t = 26 Divide each side by '2'. t = 13 Simplifying t = 13
| 3x-2=4x+15 | | -5(x+2)-4=-29 | | Ad=12ax+14 | | n(n+1)(n-1)(n-2)=840 | | 1=g/2-2 | | (10n)3/2 | | 0=-5x-(625/10) | | -5=5-2d | | -w/3=12 | | 2B-11=88 | | -4/7x=16/27 | | 2v+1=10 | | 2x^2+2x+75=0 | | y/4=14 | | (2+w)(4w-5)=0 | | 20x-23=7 | | 6(X+5m+4)= | | 9=5+2t | | 2[2y+5]=26 | | c=cx+n | | X^9/x^2 | | 2xy+6a=8x | | v^2+6-7=0 | | 19n=190 | | 3=2w-1 | | 7=v-8 | | -4k+2(5k-6)=-3k-38 | | 1/2(2)-3=y | | 2/3×9/20 | | -7v=140 | | D+30=9 | | C+24=-10 |